Human METTL16 is a N6‐methyladenosine (m6A) methyltransferase that targets pre‐mRNAs and various non‐coding RNAs. (19th October 2017) - Warda, Ahmed S; Kretschmer, Jens; Hackert, Philipp; Lenz, Christof; Urlaub, Henning; Höbartner, Claudia; Sloan, Katherine E; Bohnsack, Markus T
Abstract: N 6 ‐methyladenosine (m 6 A) is a highly dynamic RNA modification that has recently emerged as a key regulator of gene expression. While many m 6 A modifications are installed by the METTL3–METTL14 complex, others appear to be introduced independently, implying that additional human m 6 A methyltransferases remain to be identified. Using crosslinking and analysis of cDNA (CRAC), we reveal that the putative human m 6 A "writer" protein METTL16 binds to the U6 snRNA and other ncRNAs as well as numerous lncRNAs and pre‐mRNAs. We demonstrate that METTL16 is responsible for N 6 ‐methylation of A43 of the U6 snRNA and identify the early U6 biogenesis factors La, LARP7 and the methylphosphate capping enzyme MEPCE as METTL16 interaction partners. Interestingly, A43 lies within an essential ACAGAGA box of U6 that base pairs with 5′ splice sites of pre‐mRNAs during splicing, suggesting that METTL16‐mediated modification of this site plays an important role in splicing regulation. The identification of METTL16 as an active m 6 A methyltransferase in human cells expands our understanding of the mechanisms by which the m 6 A landscape is installed on cellular RNAs. Synopsis: METTL16 is a human m 6 A methyltransferase that targets pre‐mRNAs, lncRNAs, and ncRNAs. METTL16 methylates A43 in the U6 snRNA sequence that base pairs with 5′ splice sites of pre‐mRNAs. The human RNA methyltransferase METTL16 is an m 6 A "writer" protein. METTL16 modifies the U6 snRNA within an evolutionarily conserved motif that base pairs with 5′ splice sites in pre‐mRNAs. METTL16 binds multiple pre‐mRNAs, primarily in introns, as well as lncRNAs and ncRNAs. Abstract : METTL16 is a human m 6 A methyltransferase that targets pre‐mRNAs, lncRNAs, and ncRNAs. METTL16 methylates A43 in the U6 snRNA sequence that base pairs with 5′ splice sites of pre‐mRNAs.